Clinical and topographical range of callosal infarction: a clinical and radiological correlation study. Issue 3 (September 1995) - Giroud, M; Dumas, R
Abstract : A prospective clinical and radiological correlation study was performed to determine the frequency, and the clinical and radiological features of callosal infarction. From 1 January 1993 to the end of December 1993 282 cases of cerebral infarction seen in the Neurology service of the University Hospital of Dijon were studied prospectively. Eight cases with callosal ischaemic lesions were identified by CT and MRI. A callosal disconnection syndrome occurred in only five of eight patients, related to a single, large infarct or several infarctions in the anterior part of the corpus callosum. Clinical features were characterised by left ideomotor apraxia, construction apraxia, and left agraphia in all five cases. Alien hand was noted in only two cases. There were gait disorders in three cases with MRI features of multiple lacunes in a large part of the corpus callosum, and also the subcortical areas of both hemispheres. It is emphasised that callosal infarctions are not rare and that they contribute to the clinical features of strokes. As well as the classic incomplete callosal disconnection syndrome, these callosal ischaemic lesions may induce non-specific gait disorders.